What factors affecting poverty rates in Indonesia? Empirical evidence from West Sumatera - Rendra Hardinata Saputro; Muhammad Arif (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — This study aims to estimate the impact of four key variables - the average length of schooling, the disaster risk index, the labor force participation rate, and the construction cost index - on the percentage of the population living in poverty.Method — This research is a quantitative study that utilizes secondary data sourced from the Central Statistics Agency (BPS) of West Sumatera and Inariks BNPB. It primarily focuses on the variable of poverty. The analytical approach adopted in this study is panel data analysis, which integrates both cross-sectional and time series data. The cross-sectional aspect of the research encompasses 19 regencies/cities within the West Sumatera Province, and the time series data extends from 2017 to 2022. All data processing and analysis are conducted using Eviews 10 software.Result — The research findings suggest that the Fixed Effects Model (FEM) is the most effective approach for analyzing regression models. The estimated results reveal that both the average length of schooling and the labor force participation rate negatively impact the percentage of the impoverished population. In contrast, the disaster risk index and the construction cost index appear to have no influence on the impoverished population percentage.Novelty — This research introduces a novel dimension to the study of poverty, focusing on disaster risk and construction factors that have not been previously explored in earlier studies.